Nadra-3D Add-On for Blender Software - Bilous, M. V. (Cybernetics and systems analysis, 2016)
Nadra-3D add-on package for Blender software is considered. This add-on allows use of Blender, TetGen, and ParaView software for data pre/post processing for finite element solver Nadra-3D, designed for simulation of spatial processes of filtration, heat transfer, and changes of the stress–strain state of multicomponent media.